Bimetallic MOF-Derived Synthesis of Cobalt-Cerium Oxide Supported Phosphotungstic Acid Composites for the Oleic Acid Esterification. (5th October 2021) - Zhang, Qiuyun; Yang, Xianju; Yao, Jiali; Cheng, Jingsong
Abstract : The impregnation of phosphotungstic acid (HPW) with porous cobalt-cerium oxide (HPW@CoCeO) has been prepared by pyrolysis of CoCe-MOF and used for the production of methyl oleate from oleic acid and methanol. FTIR, XRD, SEM, TEM, N2 adsorption/desorption, and NH3 -TPD were characterized for the prepared composites. Simultaneously, the effects of reaction time, substrate molar ratio, temperature, and catalyst loading on catalytic activity were highlighted, and the conversion of 67.2% was reached after 4 h at 60°C. Importantly, HPW@CoCeO was reusabe and reused more than eight times, and the oleic acid conversion could be maintained at 61.8% without significant activity loss. Thus, the HPW@CoCeO composite could be used as acid catalysts for sustainable energy production.